Analisis Kinerja Manajemen Tenaga Pendidik dan Kependidikan di SDN Lontar II Surabaya - Windasari, Windasari; Vrachmadhani, Viojezsha Valibra; Risky, Bella Adinda (MASALIQ, 2024)
This study aims to analyze the performance of teacher and educational management in SDN Lontar II Surabaya, focusing on the effectiveness of human resource management and strategies for teacher professionalism development. The research method used is a case study in several primary schools in a specific region. Data were collected through observations, interviews, and document analysis. The results of the analysis indicate that the performance of teacher and educational management in primary schools still faces several challenges, including lack of administrative support, limited resources, and the need for further training and development for teachers. Therefore, it is suggested that schools improve human resource management strategies, provide relevant training, and encourage teacher participation in professional development activities.